Detection of phosphate solubilizing bacteria from rhizospheric soil of agricultural crops in Erode district: Life Sciences-Botany for Medicinal science - S, Sharmila.; M, Anusha.; .S, Vinothini; .E.K, Ramya; .S, Mownika (International Journal of Life Science and Pharma Research, 2021)
Phosphorus is a second key plant nutrient and the ‘kingpin’ in Indian agriculture, occupies an exclusive position both in conventional as well as in alternative agriculture. However, the phosphate solubilizing bacteria (PSB) converts the insoluble phosphate into biologically available form through the production of organic acids. Hence, the present study explored the presence of PSB from the Karavalasu agricultural field, Sivagiri, Erode District. The percentages of bacterial solubilization were 14.40 % to 60.70 % in non rhizospheric and rhizospheric crops adhering to root soils respectively.Out of 14 morphologically distinct isolates of PSB, two isolates (PSB8 and PSB11) displayed high P solubilization efficiency on solid medium amended with tricalcium phosphate Ca3(PO4)2 as the insoluble source (0.2 %). They were further characterized and continued with identification used by Picovskaya’s selective medium. The selective medium was incubated for 48 hours at a temperature of 37°C. The characterization was done for two strains by looking at the colony morphology and biochemical properties. The isolates showed the optimum pH for growth of the organism was pH 7 and the optimum temperature was 37 °C. Two strains exhibited significant release of P at the concentrations of 1.96 and 2.26 mg/l by PSB – 8 and PSB – 11 respectively on 10th day of incubation in broth medium amended with Ca3(PO4)2. The strains released acids as evident by decline in pH of the broth medium. They also secreted IAA with the maximum of 17.06 mg/l by PSB - 8 with Ca3(PO4)2 as a source of P. The potential strains for P solubilization were identified using 16S rRNA as Bacillus megaterium and Pseudomonas aeruginosa for further application as bioinoculants to agricultural fields. Finally we afford some indication that the use of Phosphate solubilising microorganisms will support sustainable agriculture and conclude that this knowledge is ready for commercial utilization in various regions worldwide. Keywords: ,